The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.heliyon.2021.e06543
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence access to and the level of participation in high value mango markets by smallholder farmers in Ghana?

Abstract: Market participation is critical to smallholder agricultural production because it stimulates increased productivity and enhances poverty alleviation. Accessibility to high value markets and participation by small-scale mango farmers in these markets in Southern Ghana are low and have received little attention on both policy and academic fronts. This study analyzed the factors that drive smallholder farmers in Ghana to participate in high value mango markets in Southern Ghana. A multistage random sampling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The study adopted the SPF model to postulate a profit function that is assumed to behave in a manner consistent with the stochastic frontier concept [30,31]. This approach has been extensively used to estimate the technical and profit efficiency of small-scale farmers across the globe [30][31][32][33][34]. The preference of this approach emanates from its parametric nature and superiority compared to other methods.…”
Section: Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The study adopted the SPF model to postulate a profit function that is assumed to behave in a manner consistent with the stochastic frontier concept [30,31]. This approach has been extensively used to estimate the technical and profit efficiency of small-scale farmers across the globe [30][31][32][33][34]. The preference of this approach emanates from its parametric nature and superiority compared to other methods.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The average years spent in school was seven years, which is equivalent to primary education and thus means spinach farmers were literate. This means that spending many years in school provided spinach farmers with managerial competence and the ability to implement innovative techniques and marketing practices [34]. Educated farmers can make informed decisions to increase production, unlike uneducated farmers [15].…”
Section: Socio-economic Characteristics Of Spinach Farmersmentioning
confidence: 99%
“…In order to comply with production standards, farmers with certified product quality will take the initiative to increase production-specific investments and upgrade product technologies for the purpose of levelling the degree of product differentiation [ 37 ]. The higher technology level of agricultural products will uniquely advantage the products, which will help to lower the access barrier to entering the broader markets [ 38 , 39 ]. Traditional distribution channels—mainly wholesale markets—did not set higher quality standards for agricultural products.…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…The development of HVMs has become an increasingly important strategy and has attracted much attention worldwide (Maspaitella, Garnevska et al 2018, Ngenoh, Kurgat et al 2019, Akrong, Mbogoh et al 2021. Participation in HVMs is an important channel to facilitate stable incomes and sustainable livelihoods for farmers (Sumari, Mishili et al 2018, Akrong, Mbogoh et al 2021. Thus, linking farmers to HVMs has become a focus of donors and non-governmental organizations (ngos) in recent years (Altenburg, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, linking farmers to HVMs has become a focus of donors and non-governmental organizations (ngos) in recent years (Altenburg, 2006). While some studies concluded that farmers would get obvious economic opportunities from being linked to HVMs (Hernandez, Reardon et al 2007, Miyata, Minot et al 2009, Rao and Qaim 2011, participation of farmers in HVMs in developing countries remains low (Akrong, Mbogoh et al 2021). Farmers play the dual role of production managers in the input market and suppliers in the output market, it is therefore of great importance to study the willingness of farmers to participate in HVMs to improve the speed and quality of development of HVMs.…”
Section: Introductionmentioning
confidence: 99%